Pendidikan Ilmiah Epistemik Siswa Studi Kasus Madrasah Aliyah Unggulan K.H. Abd. Wahab Hasbulloh - Imam Taufiq; Teguh Shalahuddin; Husni Thowiyyah; Agus Suprayogi (YASIN, 2026)
Epistemic scientific education has been widely discussed in various studies; however, research that specifically examines students’ epistemic scientific education practices in the context of outstanding Madrasah Aliyah remains limited. This study aimed to explore and describe how epistemic scientific education is developed and practiced by students in the process of scientific writing at Madrasah Aliyah Unggulan K.H. Abd. Wahab Hasbulloh (MAUWH). A qualitative approach with a case study design was employed, involving students and scientific writing supervisors selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis of students’ scientific papers, then analyzed qualitatively to identify patterns of learning and habituation of scientific practices. The findings show that students’ epistemic scientific abilities are formed through individually conducted learning and scientific writing processes, in which students are trained to formulate problems, trace scientific sources, and construct arguments systematically. These results contribute to the development of epistemic scientific education theory and broaden understanding of the practical implementation of epistemic scientific learning in the madrasah context. The study concludes that learning and habituation of scientific practices play a crucial role in shaping students’ epistemic abilities and recommends the strengthening of research-based learning in Madrasah Aliyah. The implications enrich the literature on epistemic scientific education and provide practical guidance for Islamic educational institutions in developing scientifically oriented learning, while also opening opportunities for further studies on more comprehensive mapping of students’ levels of epistemic scientific ability.